2020
DOI: 10.1182/bloodadvances.2019001272
|View full text |Cite
|
Sign up to set email alerts
|

Identification of germline variants in adults with hemophagocytic lymphohistiocytosis

Abstract: Key Points Some germline variants are predicted to disrupt protein function in HLH-associated genes. Such variants are neither enriched in adult-onset HLH nor associated with specific clinical or laboratory features of HLH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…We analyzed a cohort of 88 adult patients who met HLH-2004 diagnostic criteria, as described previously. 2 The average age of the cohort was 54 years (range, 18-81), and the majority were male (55%). A precipitating etiology was identified in most cases (77%), with some having multiple etiologies (16%), including malignancy (44% lymphoid, 9% myeloid, and 3% solid), infection (30%), and autoimmune disease (17%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed a cohort of 88 adult patients who met HLH-2004 diagnostic criteria, as described previously. 2 The average age of the cohort was 54 years (range, 18-81), and the majority were male (55%). A precipitating etiology was identified in most cases (77%), with some having multiple etiologies (16%), including malignancy (44% lymphoid, 9% myeloid, and 3% solid), infection (30%), and autoimmune disease (17%).…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA was isolated from peripheral blood and bone marrow aspirate samples (DNeasy Kit; Qiagen, Hilden, Germany) of patients who met HLH-2004 diagnostic criteria treated at 5 clinical institutions between 2001 and 2018. 2 In the 2016 revised classification, analysis of histiocytoses and neoplasms of the macrophagedendritic cell lineages, secondary HLH, or HLH of unknown origin were assigned to group H. 7 Hybrid capture of exons from 98 genes was performed on the genomic DNA samples with a custom SureSelect system (Agilent Technologies, Santa Clara, CA; supplemental Table 1, available on the Blood Web site) followed by library preparation and sequencing on the Illumina platform (San Diego, CA). Mutations were identified with Varscan 2.2.3 and annotated using ANNOVAR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five types of hereditary or familial HLH were described in the literature [ 2 ] and they are caused by mutations in adaptor related protein complex 3 subunit beta 1 ( AP3B1 ), biogenesis of lysosomal organelles complex 1 subunit 6 ( BLOC1S6 ), Bruton’s tyrosine kinase ( BTK ), CD27 , interleukin-2 (IL-2) receptor subunit gamma ( IL2RG ), IL-2 inducible T-cell kinase ( ITK ), lysosomal trafficking regulator ( LYST ), magnesium transporter 1 ( MAGT1 ), perforin 1 ( PRF1 ), RAB27A, member Ras oncogene family ( RAB27A ), SH2 domain containing 1A ( SH2D1A ), solute carrier family 7 member 7 ( SLC7A7 ), syntaxin ( STX ) 3 , STX11 , STX binding protein 2 ( STXBP2 ), Unc-13 homolog D ( UNC13D ), and X-linked inhibitor of apoptosis ( XIAP ) genes. Primary HLH is autosomal recessive inherited and diagnosis is established by molecular genetic testing.…”
Section: ⧉ Introductionmentioning
confidence: 99%
“…One limitation of our study is not being able to examine whether germline variants in genes associated with familial HLH are enriched in patients with NKTCL-associated HLH. However, recent studies have not shown an association of biallelic pathogenic variants in HLH-associated genes with adult HLH, albeit in cohorts that comprise a mixture of lymphoma and non-lymphoma subtypes (9,10). Ultimately, additional efforts to define disruptive variants in a larger number of genes, in expanded cohorts of adults with lymphoma associated HLH, may further refine our understanding and treatment of this devastating condition.…”
mentioning
confidence: 99%